Unveiling the Therapeutic Potential of Ipomoea Batatas Lam: A Journey From Preclinical Research to Clinical Applications - Singla, Riya; Kamboj, Sonia; Duvey, Brijesh Kumar; Bhargava, Anurag; Chaudhary, Jasmine; Jain, Akash (Scripta Medica, 2026)
Ipomoea batatas Lam, commonly known as sweet potato, has garnered recognition for its significant therapeutic potential, which can be largely ascribed to its abundant array of bioactive secondary metabolites. Among these phytoconstituents, flavonoids, anthocyanins, carotenoids and terpenoids have been shown to possess notable pharmacological properties through preclinical investigations. Evidence from in vitro studies utilising cell culture models indicates that these compounds exhibit robust antioxidant and anticancer activities, with anthocyanins in particular being reported to inhibit the proliferation of cancer cells. Furthermore, in vivo experiments substantiate the diverse therapeutic efficacy of Ipomoea batatas, revealing its anti-obesity, hypoglycaemic, hepatoprotective and anti-arthritic properties. Advancements in the understanding of these therapeutic attributes have facilitated the progression of extracts from Ipomoea batatas to clinical evaluation with subsequent assessment of safety, toxicity, pharmacokinetics and benefit-risk ratios. The transition from preclinical research to clinical validation accentuates its relevance in the realm of metabolic health, especially in combating obesity, liver dysfunction and diabetes. The successful completion of Phase III clinical trials has resulted in the introduction of plant-based antidiabetic formulations into the market, thereby reinforcing the pharmacological significance of this plant. Nevertheless, despite these promising developments, the complex interactions between the phytoconstituents and their corresponding therapeutic effects warrant further investigation. Continued research in this domain is essential, as it promises not only to enrich the understanding of the medicinal properties of Ipomoea batatas but also to reveal innovative therapeutic applications. Such endeavours will likely establish Ipomoea batatas as an esteemed natural resource within contemporary medicine.